IOT-ENABLED SMART CITIES: CHALLENGES AND INNOVATIONS IN URBAN INFRASTRUCTURE: - Syed Tahir Ali Qureshi (Bulletin of Engineering Science, Technology and Industry, 2024)
The rapid urbanisation and technological advancements have led to the emergence of smart cities, where the Internet of Things (IoT) plays a critical role in transforming urban infrastructure. IoT-enabled smart cities aim to enhance quality of life by leveraging interconnected devices, real-time data analysis, and automated systems. However, these advancements come with challenges such as data security, system integration, and infrastructural compatibility. This article explores the challenges and innovations associated with IoT-enabled urban infrastructure, focusing on transportation, energy management, waste management, and public safety. The article concludes with potential future directions for sustainable and efficient urban development.